2018
DOI: 10.7759/cureus.3446
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases with Incidental Finding of Large Asymptomatic Intradural Lumbar Tumors

Abstract: Benign lumbar intradural tumors are statistically uncommon and usually present with complaints of back pain with or without radicular neurological complaints. This report involves two separate patients that were found incidentally to have large intradural tumors without any neurologic complaints. In both cases the tumors were discovered when having magnetic resonance imaging (MRI) after minor auto accidents. Neither patient had any pre-existing lumbar or neurologic complaints. The report will review the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The discovery of spinal tumors and other intra and extraspinal abnormalities during a radiologic examination being performed for other reasons is well-recognized and common with the use of magnetic resonance imaging (MRI) in the routine work-up of patients for lumbar and/or radicular pain [1]. In a large series of MRI studies, tumors were incidentally found in only 0.05% [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of spinal tumors and other intra and extraspinal abnormalities during a radiologic examination being performed for other reasons is well-recognized and common with the use of magnetic resonance imaging (MRI) in the routine work-up of patients for lumbar and/or radicular pain [1]. In a large series of MRI studies, tumors were incidentally found in only 0.05% [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a large series of MRI studies, tumors were incidentally found in only 0.05% [2]. Often, after an injury, and especially with fractures, computerized tomography (CT) or MRI scans are performed and other spinal pathologies, such as Tarlov cysts, vertebral hemangiomas, lumbar stenosis, and, rarely, unsuspected tumors can be found [1,3]. Tumors can present with back pain, with or without neurologic symptoms, including radicular complaints and, especially when the tumor is large, cauda equina syndrome (CES) [4].…”
Section: Introductionmentioning
confidence: 99%